Exploring the productivity and profitability of small-scale communal irrigation systems in Sub-Saharan Africa - Bjornlund, Henning; Pittock, J. (Informa UK Limited, 2017)
This special issue explores the challenges associated with increasing the productivity and profitability of small-scale communal irrigation systems in a world with growing demand for food and scarce water supplies. Case studies from Mozambique, Tanzania and Zimbabwe in south-eastern Africa are used to detail the challenges, opportunities and possible solutions.